Relationship between Work-Life Balance Programs and Employee Productivity in Kenya - Kimani, Bonface (European Journal of Human Resource, 2024)
Purpose: The aim of the study was to assess the relationship between work-life balance programs and employee productivity in Kenya. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Organizations that implement comprehensive work-life balance programs, including flexible working hours, telecommuting options, and childcare support, often observe improved employee performance and engagement. These programs help reduce stress and burnout, enabling employees to manage their professional and personal responsibilities more effectively. Consequently, employees exhibit higher levels of job satisfaction and motivation, which translates into increased productivity. Studies also show that employees who experience a balanced work-life dynamic are less likely to experience absenteeism and turnover, further contributing to organizational efficiency and performance. Overall, the integration of work-life balance initiatives within organizational policies not only fosters a supportive work environment but also enhances overall employee productivity. Implications to Theory, Practice and Policy: Conservation of resources (COR) theory, social exchange theory and self-determination theory may be used to anchor future studies on assessing the relationship between work-life balance programs and employee productivity in Kenya. Organizations should adopt a tailored approach when implementing work-life balance programs, considering the unique needs and preferences of their workforce. Policymakers have a vital role in promoting work-life balance programs, and they should advocate for legislation that encourages organizations to adopt these initiatives.